AVALIAÇÃO DE LIVROS NA ÁREA DE SERVIÇO SOCIAL: reflexões (im)pertinentes - Maria Lúcia Teixeira Garcia (Universidade Federal do Maranhão, 2018)
The purpose of this article is to present some information and considerations that can stimulate reﬂections about the process of evaluation of books in the ﬁeld, realized during the 2017 quadrennial at CAPES. The paper indicates the themes addressed, revealing some impasses and diﬃculties experienced by the programs.Forthisreason, our evaluation consideredsocialservicenorms,par- ticularly the Curriculum Guidelines of the ABEPSS, bibliographic and docu- mentresearchanddataproducedbyCAPESconcerningthepasttwoevaluative cycles (TheEvaluative Reports from theﬁeld ofSocial Work for the Triennials 2010 and 2013, Quadrennial 2017 and the analytic charts for the evaluation of books from 2010, 2013 and 2017). The study also sought to indicate some of the future limits to the maintenance of the current form of evaluation of books, considering the eﬀorts and costs that this raises for the programs, the ﬁeld and the professors involved.